Application Model of Learning B-O-R-N With Moodle Basic For Improving Student Learning Result in Operating System - Julio Leonardo; Agus Efendi; Taufik Lilo Adi Sucipto (Journal of Informatics and Vocational Education, 2018)
This research is Classroom Action Research (CAR) by using B-O-R-N model based on moodle Each cycle consists of planning stage, action implementation stage, observation stage, and reflection phase. Subjects in this classroom action research were class X students RPL A SMK Negeri 2 Karanganyar academic year 2016/2017 with the number of learners 36 learners. Data collection was done by using documentation techniques, interview techniques, online test techniques and group discussion results. The observed aspects consist of cognitive, affective and psychomotor aspects. Data analysis technique used is descriptive comparative. Compare students' work results by using percentage figures. The results obtained as follows: 1) achievement of cognitive aspects on precycle 38.89% in the first cycle increased 52.79% and again increased in the second cycle of 77.78%. 2) achievement of affective aspect on precycle = 19,44%, cycle I = 61,11%, and cycle II = 86,11%. 3) psychomotor aspect achievement on precycle = 41.67%, cycle I = 69.44%, cycle II = 83.33%. Based on the result of the research, it can be concluded that the learning model of B-O-R-N assisted by moodle media is effective in improving learners' learning outcomes in the subject matter of administration of open source operating system class X RPL A SMK Negeri 2 Karanganyar periode 2016/2017.